THE USE OF MALAY MODALITIES IN ABSTRACTS OF PROCEDA SOCIAL AND BEHAVIORAL SCIENCES JOURNALS - Mirsa Umiyati; Rika Purnama Sari (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
An abstract of research article should give information obviously. Modalities assist researcher to provide certain obvious information in an abstract. This study important to carry out to identify the types and functions of Malay modality used in abstracts of Proceda Social and Behavioral Sciences journal and examine the types of modality that are dominantly used in abstracts of Proceda Social and Behavioral Sciences journal. Qualitative and quantitative methods are the design of this study. Data of this study are abstracts from 18 articles of Proceda Social and Behavioral Sciences journal published by Elsevier. The data were analyzed using intralingual equivalent method by applying hubung banding menyamakan (HBS) technique. The results of the analysis are then presented using informal methods. Based on the results of the study, it can be concluded that there are four types of Malay modalities used in the abstracts of the Proceda Social and Behavioral Sciences journal, namely intentional, epistemic, deontic, and dynamic modalities. In addition, phrasal modals or periphrastic modals are found in the abstract in question. The dominant type of modality used in the abstract is intentional modality of 31%. Furthermore, the Malay modality used in the abstract articles of the Proceda Social and Behavioral Sciences journal indicates the existence of this modal function in abstract construction. The functions of the modals are to inform the aims or objectives, focus, problem, background and gap, method, technique analysis, and suggestion of the research.Keywords: abstract, malay, types of modalities PENGGUNAAN MODALITAS BAHASA MELAYU PADA ABSTRAK JURNAL PROCEDA SOCIAL AND BEHAVIORAL SCIENCES AbstrakAbstrak dalam artikel penelitian harus memberikan infomasi yang jelas. Modalitas dapat membantu peneliti untuk memberikaninformasi tertentu secara jelas dalam absrtrak. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis dan fungsi modalitas bahasa Melayu yang digunakan pada abstrak jurnal proceda social and behavioral sciences dan mengkaji jenis modalitas yang dominan digunakan pada abstrak jurnal proceda social and behavioral sciences. Metode qualitative dan quantitative adalah desain dari penelitian ini. Data penelitian ini adalah abstrak dari 18 artikel pada jurnal Proceda Social and Behavioral Sciences yang berbahasa melayu yang dipublikasikan oleh Elsevier. Dalam menganalisis data, digunakan metode padan intralingual dengan menerapkan teknik hubung banding menyamakan (HBS). Hasil analisis kemudian disajikan dengan menggunakan metode informal. Berdasarkan hasil penelitian, dapat ditarik kesimpulan bahwa terdapat empat jenis modalitas bahasa Melayu yang digunakan pada abstrak jurnal Proceda Social and Behavioral Sciences, yaitu modalitas intensional, epistemic, deontic, dan dinamik. Selain itu ditemukan phrasal modals or periphrastic modals pada abstrak yang dimaksud. Jenis modalitas yang dominan digunakan dalam abstrak tersebut ialah modalitas intensional sebesar 31%. Selanjutnya, modalitas bahasa Melayu yang digunakan pada abstrak artikel jurnal Proceda Social and Behavioral Sciences mengindikasikan adanya fungsi modal tersebut pada konstruksi abstrak. Kata kunci: abstrak, bahasa melayu, jenis modalitas